2011
DOI: 10.3855/jidc.1675
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HPV: a cross-sectional study in women with normal cytology in north-central Morocco

Abstract: Introduction: Epidemiological studies have shown the association between risk of developing cervical cancer and the persistence of high-risk papillomavirus types in addition to some co-factors. However, little is known about co-factors associated with human papillomavirus (HPV) infection, especially in developing countries. This study aims to determine HPV status and associated risk factors in women with normal cytology living in the north-central area of Morocco. Methodology: From February 2007 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
4
10
2
Order By: Relevance
“…In this study, we found a significantly higher 481 prevalence of HPV infection in women living with HIV/AIDS (74.50%) and HR-HPV types were present in the vast majority of cases (75%). These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, we found a significantly higher 481 prevalence of HPV infection in women living with HIV/AIDS (74.50%) and HR-HPV types were present in the vast majority of cases (75%). These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28].…”
Section: Discussionsupporting
confidence: 81%
“…This result seems to be in line with previous reports [36,44]. In contrast, this molecular epidemiology profile was not consistent with observed in HIV-negative women [6][7][8] or women with CC in Morocco [9][10][11][12], in whom HPV 16 and 18 predominate. Such discrepancies between groups (HIVpositive and HIV-negative) has been reported in previous studies and may partly due to immune system deficiency [30,45].…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…We are in the process of starting a prospective study to measure E6/E7 mRNA [28] in fresh cervical specimens and then follow those positive cases to explore the progress to cervical carcinoma. We also would suggest that screening and triage of older women should be implemented soon, as planned in Morocco [29] and as performed in the developed world [30].…”
Section: Discussionmentioning
confidence: 99%
“…The range of HPV infection in cytologically normal women was reported to range between 1.4% in Spain to 25.6% in Nigeria. 9 Molano et al 10 reported the prevalence of HPV in 1,859 subjects with normal cytology was 14.8%, while Bennani et al 11 reported a very high rate, which was 42.5%. HPV prevalence in cytologically normal women in Honduras as reported by Tabora et al was even as high as 51%.…”
Section: Discussionmentioning
confidence: 99%